Pakeliran Layar Lebar: A development of the Balinese shadow puppet - Marajaya, I Made (Linguistics and Culture Review, 2023)
This study aims to describe the development model for Balinese shadow puppet shows in the era of globalization. For nearly thirty years, Balinese shadow puppet performances marked ups and downs of requests from the public to respond to and watch them, especially for traditional performances. For this reason, to restore the Balinese shadow puppets to revival in the era of globalization, young puppeteers try to save them by exploring, preserving, and developing shadow puppet shows by creating a new work called Pakeliran Layar Lebar. The work on Pakeliran Layar Lebar is one of the genres of traditional wayang art that has appeared since 1988 under the encouragement of Prof. Dr. I Made Bandem, who at that time was chairman of the Denpasar Indonesian Art College. Visually, the form of Pakeliran Layar Lebar is very much different from the traditional ones. In its presentation, dance artists, musicians, puppeteers, theatres, narrators, and interpreters supported Pakeliran Layar Lebar with advanced technology such as; lighting, scenery, sound system, computer, LCD, and so on also support. Pakeliran Layar Lebar is classified as a balih-alihan (spectacle) art, so it functions as a medium for education, entertainment, and artistic creativity with an aesthetic nuance.